Robust optimal design via space mapping: urgent and future needs - Bandler, John W. (Bandler Corporation, 2007)
A review of the state of the art in space mapping technology, and why space mapping works. We discuss space mapping as a natural mechanism for the brain to relate objects or images with other objects, images, reality, or experience; that "experienced" engineering designers (experts), knowingly or not, routinely employ (or have employed) space mapping to achieve complex designs; that with virtually no mathematics, simple everyday examples illustrate space mapping, e.g., archery, stone-throwing, cheese-cutting, log-cutting, cake-cutting, shoe-selection; and that space mapping offers a quantitative explanation for the engineer’s mysterious "feel" for a problem. We conclude with conjectures and proposals.
Slides for a plenary presentation on the topic of "Why engineering design through space mapping works: An engineer's interpretation." The occasion: Workshop on Robust Multiobjective Design Optimization with Simulation at the Fraunhofer-Chalmers Research Centre for Industrial Mathematics (FCC), Gothenburg, Sweden, December 3-4, 2007.
Keywords: space mapping; surrogate models; human brain; engineering design; neuroscience; Broyden update; cognition; predictive models